SISTEM INFORMASI SURAT KELUAR BERBASIS WEB MENGUNAKAN XAMPP DAN MySQL DI SD LANGENSARI KOTA CIMAHI - Rifqi Fauzan, Muhammad; Agustin, Cahyadi (INFOKOM (Informatika & Komputer), 2024)
The management of outgoing correspondence is essential for maintaining efficient communication and documentation within educational institutions. This study examines the implementation and impact of an outgoing correspondence information system at SD Langensari. The system, designed to streamline the process of generating, tracking, and archiving outgoing letters, includes functionalities for creating cover letters, notifications, and certificates. By automating and standardizing these processes, the system aims to enhance the accuracy and efficiency of communication, reduce manual errors, and ensure compliance with administrative standards. The research explores the system’s role in improving organizational transparency, facilitating record-keeping, and supporting professional communication practices. Additionally, the study assesses the system’s integration with digital tools and its adaptability to the evolving technological landscape. The findings indicate that the system has significantly improved the management of outgoing correspondence, leading to better operational efficiency and increased reliability in communication at SD Langensari.